PRAKIRAAN HARGA BAHAN BAKAR GAS YANG KOMPETITIF UNTUK PEMBANGKIT LISTRIK DENGAN PENDEKATAN NET BACK VALUE - Azwin, Rahmat
Abstract: Diversification program on fuel that was done by the Government has successfully reduced fuel oil (BBM) consumption and optimize a usage of natural gas that has 3 times more reserve in comparison with oil. At this moment, power plants that use natural gas give the biggest contribution and achieve 40 % of national power production. Considering that price of natural gas is in US Dollar currency, the weakening of Rupiah against Dollar causes the price of natural gas become very expensive and will not be competitive. A study in estimating a reasonable price of natural gas to make a power plant that use this still capable to compete with other type of power plant. A natural gas price is estimated based its on economic value. Using Net Back Value method, an estimated of competitive price of natural gas for power plant by comparing generation cost of Combined Cycle Power Plant (PLTGU) with natural gas is compared with the cost of Steam Coal Power Plant (PLTU). To seek a behavior system and closer to real problems, simulation method is used. Based on reality both power plants above have different in quality of environment impact, it needs to calculate a social cost value in the cost structure of PLTU with coal plant. To estimate the value of that social cost, Delphi Method approached is used. The study concludes an estimation of competitive natural gas price to used for power plant is in average price of 2.32 US$/MCF. Based on 3 (three) types of scenario by using regression method on the result of the above simulation, the optimist scenario gives a price of 2.10 US$/MCF, medium scenario gives 1.93 US$/MCF and pessimist gives 1.87 US$/MCF. With those results, it concludes that a price of natural gas that applicable for PT PJB nowadays, 2.53 US$/MCF, is still above economic value for using in a power plant as studied. Considering that capacity factor is a factor that has strongest correlation in influencing estimation of natural gas price, a further study should be need for estimating long-term power capacity required in Jawa Bali Interconnection System to predict the market segment more accurately.